Analysis of the novel “The Mystery of the Wooden House” by Havva Tekin in terms of values and Turkish education - Yeniasır Mustafa; Gökbulut Burak; Öznur Şevket (SHS Web of Conferences)
Literary works play a very important role in helping children gain the following objectives of the Turkish language teaching curriculum permanently: developing listening, speaking, reading and writing skills, developing imagination, reading comprehension and text evaluation from a critical perspective, and ensuring that students give importance to national, spiritual, moral, historical, cultural, and social values. Therefore, after lullabies and fairy tales, children should be introduced as early as possible to high-quality stories and novels that reflect the narrative power of the Turkish language, are suitable for their language development and needs, and appeal to their world of thought. Works produced in the field of children’s literature both contribute positively to children’s emotional and intellectual worlds and prepare them for life. Novels, especially those that take their subject from life and address basic values such as friendship, love, honesty, justice, patriotism, and benevolence have a very important role to play in children’s development and in their future academic lives. Havva Tekin made an important contribution to Turkish Cypriot children’s literature with her novels “Children of the Green Island”, “Tarajar beyond the Seas” and “The Mystery of the Wooden House”. With her novel titled “The Mystery of the Wooden House”, which is the subject of this study, the author has both shown the expressive power of Turkish to children and made an important contribution to their growth with the values she discussed.